2005
DOI: 10.1073/pnas.0502183102
|View full text |Cite
|
Sign up to set email alerts
|

Cationic liposome–microtubule complexes: Pathways to the formation of two-state lipid–protein nanotubes with open or closed ends

Abstract: Intermolecular interactions between charged membranes and biological polyelectrolytes, tuned by physical parameters, which include the membrane charge density and bending rigidity, the membrane spontaneous curvature, the biopolymer curvature, and the overall charge of the complex, lead to distinct structures and morphologies. The self-assembly of cationic liposome-microtubule (MT) complexes was studied, using synchrotron x-ray scattering and electron microscopy. Vesicles were found to either adsorb onto MTs, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 41 publications
10
98
0
Order By: Relevance
“…2D, bottom profile) (0-0.46 wt% of 20k PEO), where DIC shows the N MT phase, fits of background-subtracted scattering corresponded to a hollow cylinder form factor, with inner radii (∼8 nm) and cylinder thickness (4.9 nm) consistent with EM data of MTs (42). This behavior is similar to previous reports of bare MTs, where SAXS profiles of the N MT phase shows no evidence of a correlation peak (5,32,40,41,43,44). At intermediate osmotic pressures (∼1-3 wt% of 20k PEO), where DIC shows bundled MTs (Fig.…”
Section: Resultssupporting
confidence: 77%
“…2D, bottom profile) (0-0.46 wt% of 20k PEO), where DIC shows the N MT phase, fits of background-subtracted scattering corresponded to a hollow cylinder form factor, with inner radii (∼8 nm) and cylinder thickness (4.9 nm) consistent with EM data of MTs (42). This behavior is similar to previous reports of bare MTs, where SAXS profiles of the N MT phase shows no evidence of a correlation peak (5,32,40,41,43,44). At intermediate osmotic pressures (∼1-3 wt% of 20k PEO), where DIC shows bundled MTs (Fig.…”
Section: Resultssupporting
confidence: 77%
“…The sequence of events outlined above leads to a strong electrostatic attraction. This type of electrostatic interaction has been observed for self-assembled complexes between membranes and a variety of anionic polymers, including DNA [64][65][66], F-actin [67], microtubules [68], and filamentous phages [69].…”
Section: Electrostaticsmentioning
confidence: 76%
“…Using synchrotron small-angle X-ray diffraction (SAXRD) and transmission electron microscopy (TEM), we found two novel structures (Raviv et al, 2005;Raviv et al, 2006). For low membrane charge density, we found that vesicles adsorb onto the MT and appear as 'beads on a rod' (BOR).…”
Section: à3mentioning
confidence: 99%
“…Tubulin was purified from bovine brains, concentrated to 45 mM, polymerized at 310 K and taxol-stabilized as described (Needleman et al, 2004b;Raviv et al, 2005). The cationic lipid used was dioleoyl(C 18:1 ) trimethyl ammonium propane (DOTAP).…”
Section: Methodsmentioning
confidence: 99%